Transformasi Digital dalam Perbankan Syariah: Strategi, Tantangan, dan Peluang Menuju Era Keuangan Inklusif: Digital Transformation in Islamic Banking: Strategies, Challenges, and Opportunities Towards and Era of Financial Inclusion - Samsiyah; Bayu Sudrajat; Fadoli; Habib Ja'far Sodiq; Erik Ma'ruf (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
Digital transformation is reshaping the Islamic banking industry through the acceleration of technology adoption, efficiency improvement, and expansion of financial inclusion. This study examines the strategies, challenges, and opportunities of digital transformation in Islamic banking using a qualitative literature-based approach. The findings show that digitalization enhances service efficiency, supports innovation, and widens access to Shariah-compliant financial services. However, issues such as limited internet infrastructure, cybersecurity risks, and insufficient digital competencies remain significant challenges. This study highlights the importance of aligning technological innovation with Shariah governance to achieve inclusive and sustainable Islamic financial development.